Searching for a route to synthesize in situ epitaxial Pr2Ir2O7 thin films with thermodynamic methods - Lu Guo (Nature Portfolio, 2021)
Abstract In situ growth of pyrochlore iridate thin films has been a long-standing challenge due to the low reactivity of Ir at low temperatures and the vaporization of volatile gas species such as IrO3(g) and IrO2(g) at high temperatures and high P O2. To address this challenge, we combine thermodynamic analysis of the Pr-Ir-O2 system with experimental results from the conventional physical vapor deposition (PVD) technique of co-sputtering. Our results indicate that only high growth temperatures yield films with crystallinity sufficient for utilizing and tailoring the desired topological electronic properties and the in situ synthesis of Pr2Ir2O7 thin films is fettered by the inability to grow with P O2 on the order of 10 Torr at high temperatures, a limitation inherent to the PVD process. Thus, we suggest techniques capable of supplying high partial pressure of key species during deposition, in particular chemical vapor deposition (CVD), as a route to synthesis of Pr2Ir2O7.